PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2023-2024 - Intan Dara Permata (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the role of profitability and liquidity in assessing the financial performance of PT Indofood Sukses Makmur Tbk during the 2023–2024 period. The research employed a descriptive quantitative method using secondary data obtained from the company’s annual financial reports. The analysis was conducted through financial ratio calculations, including profitability ratios consisting of gross profit margin, net profit margin, Return on Investment, Return on Equity, and Earnings per Share, as well as liquidity ratios consisting of current ratio, quick ratio, and cash ratio. The results show that the company’s profitability improved in 2024 compared to 2023. Gross profit margin increased from 32.3% to 34.7%, net profit margin rose from 7.3% to 7.5%, ROI increased from 6.3% to 6.7%, ROE increased from 11.8% to 12.5%, and earnings per share increased from Rp928 to Rp984. Liquidity performance also strengthened, as reflected in the increase of current ratio from 192.0% to 215.0%, quick ratio from 145.5% to 166.6%, and cash ratio from 86.8% to 104.4%. These findings indicate that PT Indofood Sukses Makmur Tbk maintained sound financial performance, supported by improved profitability and stronger short-term financial capability. Keywords: Profitability, Liquidity, Financial Performance, Financial Ratios, PT Indofood Sukses Makmur Tbk.